Gradivo za favno hroščev (Coleptera) Slovenije - Vienna, Pierpaolo (Scopolia, 2008)
Based on the latest research and data from literature, index file and collections, the authors present 86 species of superfamily Hysteroidea of Slovenia. A further 4 species were found in the vicinity of its borders (up to20 km away). The following 41 species are stated or confirmed as part of theSlovenian fauna for the very first time: SPHAERITIDAE: Sphaerites glabratus(FABRICIUS, 1792); HISTERIDAE: Epierus comptus ERICHSON, 1834, Platysoma (Cylister) angustatum (HOFFMANN, 1803), Margarinotus (Ptomister) terricola (GERMAR, 1824), M. (P.) striola succicola (THOMSON, 1862), M. (Eucalohister) bipustulatus (SCHRANK, 1781), M. (Paralister) neglectus (GERMAR, 1813), M. (P.) ventralis (MARSEUL, l854), M. (P.) ignobilis (MARSEUL,1854), M. (P.) punctiventer (MARSEUL, 1854), M. (Grammostethus) ruficornis (GRIMM, 1852), M. (Promethister) marginatus (ERICHSON, 1834), Hister bissexstriatus FABRICIUS, 1801, H. funestus ERICHSON, 1834, H. sepulchralis ERICHSON, 1834, Atholus praetermissus (PEYRON, 1856), Dendrophilus punctatus punctatus (HERBST, 1792), Carcinops pumilio (ERICHSON, 1834), Paromalus (Paromalus) parallelepipedus (HERBST, 1792), Abraeus (Abraeus) perpusillus (MARSHAM, 1802), A. (A.) roubali OLEXA, 1958, Plegaderus(Plegaderus) saucius saucius ERICHSON, 1834, P. (P.) vulneratus (PANZER,1797), P. (P.) caesus (HERBST, 1792), P. (P.) discisus ERICHSON, 1839,Acritus (Acritus) hopffgarteni (REITTER, 1878), A. (A.) komai LEWIS, 1879, A. (Pycnacritus) homoeopathicus WOLLASTON, 1857, Teretrius (Teretrius) fabricii MAZUR, 1972, Gnathoncus nannetensis (MARSEUL, 1862), G. communis (MARSEUL, 1862), G. buyssoni AUZAT, 1917, G. nidorum STOCKMANN, 1957, Myrmetespaykulli KANAAR, 1979, Saprinus (Saprinus) maculatus (P. ROSSI, 1792),S. (S.) vermiculatus REICHARDT, 1923, S. (S.) politus politus (BRAHM, 1790), S. (S.) immundus (GYLLENHAL, 1827), Hypocaccus (Hypocaccus) rugifrons rugifrons (PAYKULL, 1798), H. (H.) metallicus (HERBST, 1792) in H. (H.) rugiceps (DUFTSCHMID, 1805). In the immediate vicinity of the Slovenian borderthe following 4 species were recorded, which have not been found in Slovenia so far: Pactolinus major (LINNAEUS, 1767), Cyclobacanius medvidovici (REITTER, 1912), Halacritus punctum (AUBÉ, 1842) in Hypocacculus (Nessus) rubripes (ERICHSON, 1834).
Keywords: biologija; biology; zoologija; zoology; hrošči; favna; Slovenia; Slovenija